A checklist of marine sponges (Porifera) of peninsula India - George, Anita M.; van Soest, Rob W.m.; Sluka, Robert D.; Lazarus, S. (Zootaxa, 2020)
An inventory of sponges from the shallow subtidal reefs of the west and east coasts of southern India is presented. The specimens offered in this paper were based on in-situ collections unlike the previous records of dry and net-entangled collections. A total of 101 species belonging to 12 orders, 22 families, 5 subfamilies and 44 genera from 4 subclasses of Class Demospongiae and one species from Class Calcarea are recorded. We recorded 18 new records to India, six new species combinations, 37 potential new records, and 40 species for the first time from the southwest coast.